A Conceptual Framework for Developing Appropriate Technology Based on Local Needs to Promote Sustainable Community Independence and Welfare - Azahra, Astrid Sulistya; Halim, Nurfadhlina Abdul (International Journal of Research in Community Services, 2026)
Appropriate technology has emerged as a strategic approach to address community development challenges, particularly in resource-constrained environments. However, many technology-based initiatives fail due to a mismatch between proposed solutions and actual community needs, as well as limited integration of local potential and participation. This study aims to develop a conceptual framework for appropriate technology that is grounded in community needs, local resources, and participatory principles. The study adopts a qualitative and conceptual approach by synthesizing findings from previous literature related to community-based development and appropriate technology. The framework is structured through three main stages: identifying community needs, analyzing local potential and resources, and designing appropriate technology based on user-centered and context-based principles. In addition, the framework incorporates participatory processes and multi-stakeholder collaboration to enhance implementation effectiveness. The results indicate that appropriate technology designed with simplicity, affordability, and adaptability can improve relevance, usability, and sustainability. The integration of local materials, skills, and cultural values strengthens community self-reliance, while participatory approaches foster ownership and increase adoption. Furthermore, the proposed framework demonstrates potential impacts on both economic and social dimensions, including increased productivity, expanded economic opportunities, improved skills, and stronger community engagement. In conclusion, this study highlights that appropriate technology should be viewed not only as a technical solution but also as a strategic tool for empowering communities and supporting sustainable development. A holistic approach that integrates local context, resources, and participation is essential to ensure long-term success and scalability.